2012
DOI: 10.1111/j.1095-8312.2011.01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in the Iberian cyprinid fish Iberochondrostoma lemmingii (Steindachner, 1866): disentangling species fragmentation and colonization processes

Abstract: Interplay between the complex geography, hydrogeomorphological history, past climatic changes, and anthropogenic pressures is likely responsible for the current diversity and species' distribution of freshwater fishes in the Iberian Peninsula. To further disentangle the evolutionary processes promoting the diversification of endemic Iberian Cyprinids through time and space, we explored the patterns of genetic diversity of the Iberian archedmouth nase, Iberochondrostoma lemmingii (Steindachner, 1866), using mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Compared to other endangered freshwater fishes from Iberia or elsewhere, I. olisiponensis shows extremely low levels of genetic polymorphism and high population subdivision (e.g. Alves et al 2001a;Salgueiro et al 2003;Mesquita et al 2005;Sousa et al 2010;Dowling et al 2012;Lopes-Cunha et al 2012;Osborne et al 2012;Sterling et al 2012;Chen et al 2013). Furthermore, in addition to the suspected old hybridization events discussed above, we present clear evidence that I. olisiponensis is currently being subjected to strong genetic assimilation through hybridization with the sympatric I. lusitanicum (Gante et al 2010 and present study).…”
Section: Taxonomic Considerationssupporting
confidence: 66%
“…Compared to other endangered freshwater fishes from Iberia or elsewhere, I. olisiponensis shows extremely low levels of genetic polymorphism and high population subdivision (e.g. Alves et al 2001a;Salgueiro et al 2003;Mesquita et al 2005;Sousa et al 2010;Dowling et al 2012;Lopes-Cunha et al 2012;Osborne et al 2012;Sterling et al 2012;Chen et al 2013). Furthermore, in addition to the suspected old hybridization events discussed above, we present clear evidence that I. olisiponensis is currently being subjected to strong genetic assimilation through hybridization with the sympatric I. lusitanicum (Gante et al 2010 and present study).…”
Section: Taxonomic Considerationssupporting
confidence: 66%
“…This genetic structure among basins, which has also been described for other Iberian freshwater fish species (Doadrio & Carmona ; Almada & Sousa‐Santos ; Lopes‐Cunha et al . ), can be linked to historical palaeogeographical factors related to the Plio‐Pleistocene formation of the current exorheic Iberian basins (Calvo et al . ) and to a lesser extent to the Mediterranean climate.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown the imprint of paleohydrological processes in the population structure of L. sclateri , characterized by a complex history leading to present‐day diverse watershed interconnections in southern Spain that have masked past relationships, in contrast with the clear patterns of population structure found in other freshwater fish populations inhabiting other areas of the Iberian Peninsula during the Plio‐Pleistocene (Doadrio & Carmona, ; Lopes‐Cunha et al., ; Robalo, Almada, Levy, & Doadrio, ). This study has also shown that the lack of a complete sampling could highly affect the explanation of the evolutionary processes that have modeled the population structure and the phylogeographic models of L. sclateri .…”
Section: Discussionmentioning
confidence: 84%